A Study on the Relationship Between TVET Skills and Employment on Self-Confidence Among Prison Inmates - ARBAIN, SITI NOOR ZUNNURAIN; Zanariah Ahmad (Research and Innovation in Technical and Vocational Education and Training, 2025)
Technic and Vocational Education and Training (TVET) plays a crucial role in helping prison inmates rebuild their self-identity and enhance self-confidence in preparation for life after release. This study was conducted to identify the level of TVET skills and its relationship with self-confidence among prison inmates. The aspects of TVET skills examined include responsibility skills, positive attitude, adaptability skills, and the ability to work with others. A total of 120 prison inmates from Penjara Simpang Renggam, Johor, were selected using purposive sampling as the study respondents. This study employed a quantitative approach with a survey design and a structured questionnaire as the primary research instrument. The collected data were analysed using the Statistical Package for the Social Sciences (SPSS) version 22. Findings revealed that overall, the level of TVET skills among inmates was high, particularly in the domains of responsibility, positive attitude, and teamwork. The level of self-confidence among the inmates was also found to be generally high. The results also indicated a positive relationship between all aspects of TVET skills and self confidence, with the highest correlation observed in teamwork skills, followed by positive attitude, responsibility, and adaptability. Overall, the study demonstrates that TVET skills significantly contribute to enhancing the self-confidence of prison inmates and have the potential to support their rehabilitation and social reintegration after release.